Grammar in context using comprehended input - Nor M.M.; Tong C.S.; Ibrahim A.H.; Jin N.Y.; Tarmizi M.A.A. (Australian International Academic Centre PTY LTD, 2023)
There have been so many ongoing disputes on different approaches to teaching grammar. This study aims to evaluate the effectiveness of teaching grammar using Gass comprehended Input technique (GCI) (1997) (implicit) and to explore the undergraduates’ perception on the GCI technique. The respondents consisted of 30 undergraduates’ who are currently pursuing their Bachelor of English. Using the qualitative method, the research instrument was a set of 23- item interview and content analysis of the students’ written work. Results showed that the teaching of grammar using explicit instructions was more preferred than implicit instruction for complex components in grammatical rules. However, implicit instruction is equally effective regardless of the proficiency levels to enable pedagogy to be executed. It is also noted that there is lots of room for improvement, since the undergraduates have a weak grasp of the basic tense aspect of English grammar. Therefore, the Malaysian Ministry of Education should consider having grammar formally taught in isolation as what was practised previously. © Australian International Academic Centre, Australia.